The International System for Reporting Serous Fluid Cytopathology: How to Incorporate Molecular Data in Cytopathology Reports - Daniel Pinto; Ashish Chandra; Fernando Schmitt (Journal of Molecular Pathology, 2021)
Serous effusion cytology is widely employed in the initial evaluation of the etiology of effusions with a high diagnostic sensitivity. To standardize practices, The International System for Reporting Serous Fluid Cytology (TIS) was developed following best international practices, the most up-to-date literature, and expert consensus. In the context of this system, ancillary techniques play an important role. Besides defining basic principles in laboratory specimen handling, adequacy criteria, and a standardized reporting terminology with five diagnostic categories, TIS provides an actionable framework for using immunohistochemical and molecular testing in effusion samples, namely, in atypical, suspicious of malignant samples. For diagnostic purposes, these tests may be employed to distinguish between a primary and secondary neoplasm, to confirm a diagnosis of malignant mesothelioma vs. reactive mesothelial hyperplasia, and to correctly classify and determine the primary location of a metastasis. Theranostic molecular tests may also be used for these samples to evaluate potential therapeutic targets. Pathologists play a central role in guiding this process by determining adequacy and selecting appropriate ancillary tests. The activity in this area of research should increase in the near future as new therapeutic targets are discovered and new drugs enter the clinical practice.